MODEL PEMBELAJARAN KOOPERATIF DENGAN MEDIA PUZZLE UNTUK MENINGKATKAN PRESTASI BELAJAR TIK SISWA SMP BINTAN - Ramlah, Ramlah (Universitas Tanjungpura, 2025)
The learning process of Information and Communication Technology (ICT) subjects tends to use more space in the computer laboratory than in the classroom. In order for ICT learning in the classroom to be active and enjoyable learning, it is necessary to choose the right media so that learning objectives can be achieved. This research was conducted at SMP Negeri 1 Bintan by taking subjects from class VIIIA students of SMP Negeri 1 Bintan in the even semester of the 2019/2020 academic year whose students' abilities for motivation to learn ICT in the classroom were still low and their mastery of the material in identifying menus and icons in Ms. Excel was still not optimal so that student learning achievement was not in accordance with expectations. The purpose of writing this research is to determine whether the Cooperative learning model with puzzle media can improve student learning achievement. The data obtained from the results of this research clearly shows an increase from the initial data, the average class only reached 71, increasing to 83. This success shows that the application of puzzle-based learning media with pictures of menu pieces and Ms. Excel icons is feasible to use and effective in improving student learning achievement.